Vulnerability of Left Amygdala to Total Sleep Deprivation and Reversed Circadian Rhythm in Molecular Level: Glut1 as a Metabolic Biomarker: - Nasehi, Mohammad; Kordestani Moghadam, Parastou; Khodagholi, Fariba; Zarrindast, Mohamad Reza (Galen Medical Journal, 2019)
Background: Sleep deprivation (SD) in the long term can cause multi-organ dysfunction as well as neurocognitive disorders. Daytime sleep or napping is a biological compensate due to insomnia or sleep deprivation. Metabolic responses to this biological rhythm may being as a biological indicator or biomarker to compare the effect of them. Glucose transporter type 1 (Glut-1) is one of the metabolic biomarkers that is affected by several conditions such as stress, seizure, malignancy, and neurocognitive disorders. We studied the effect of SD, circadian reversed (R) and napping models on the Glut-1 expression level in the right and left amygdala. Materials and Methods: Sixty-four Wistar rats were divided into eight groups as follow: Intact group that rats were placed in a cage without any intervention. In the sham group, rats were on the stable pedal of the SD apparatus (turn off). Experimental groups include total SD48, total SD48- (plus short nap), total SD48+ (plus long nap), R48, R48- (plus short nap), and R48+ (plus long nap).The Glut-1 expression level in the right and left amygdala were measured by western blotting. Results: Our findings demonstrated the significant effect of both SD for 48 hours and reversed circadian on the expression of Glut-1 from sham and intact groups. The long nap plus them could decrease the elevation of Glut-1 in the left amygdala. However, the short nap could not reduce this elevation of Glut-1. Conclusion: Left amygdala is vulnerable to the fluctuation of hypothalamic-pituitary-adrenal axis and stress. In other words, sleep disorders are affecting by Glut-1 as a metabolic biomarker in left amygdala alone. [GMJ.2019;8:e970]Â 